Pengaruh Keputusan Pendanaan, Kebijakan Dividen, Dan Risiko Bisnis Terhadap Nilai Perusahaan - Marianna Vinsencia; Intan Rahma Sari (CV. ITTC INDONESIA, 2025)
This study aims to examine the influence of funding decisions, dividend policies, and business risks on company value. Funding decisions are measured using Dividend Equity Ratio (DER), dividend policy is measured using Dividend Yield (DY), business risk is measured using Degree Operating Leverage (DOL), and company value is measured using Tobin's Q. This type of research is associative research with quantitative methods. The population of this study is healthcare sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2024, which is 38 companies. Sampling was done using the purposive sampling method and a sample of 8 companies was obtained, so that the number of data obtained with an observation period of 5 years was 40 data. The data analysis technique in this study uses panel data regression analysis processed through Eviews 12. The results of the study show that partially funding decisions have a significant negative effect on the company's value (Tobin's Q), dividend policy has a significant negative effect on the company's value, and business risk has a positive effect on the company's value. Based on the results of the F test, the variables of funding decision (DER), dividend policy (DY), and business risk (DOL) produced a regression model that is suitable for use in this study as a basis for decision-making.